2020
DOI: 10.3389/fnins.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Therapeutic Strategies for Anorexia Nervosa: Insights From Psychedelic Medicine and Animal Models

Abstract: Anorexia nervosa (AN) has the highest mortality rate of any psychiatric disease, yet available pharmacological treatments are largely ineffective due, in part, to an inadequate understanding of the neurobiological drivers that underpin the condition. The recent resurgence of research into the clinical applications of psychedelic medicine for a range of mental disorders has highlighted the potential for classical psychedelics, including psilocybin, to alleviate symptoms of AN that relate to serotonergic signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 84 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…For example, preclinical efficacy has been shown in inflammatory conditions such as high-fat diet-induced obesity and diabetes (Flanagan et al, 2019b), gut inflammatory challenges (Nau et al, 2013(Nau et al, , 2015, and asthma (Flanagan et al, 2019a). Possible utility in other psychiatric conditions, such as eating disorders, has been hypothesized and should be further explored (Foldi et al, 2020).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…For example, preclinical efficacy has been shown in inflammatory conditions such as high-fat diet-induced obesity and diabetes (Flanagan et al, 2019b), gut inflammatory challenges (Nau et al, 2013(Nau et al, , 2015, and asthma (Flanagan et al, 2019a). Possible utility in other psychiatric conditions, such as eating disorders, has been hypothesized and should be further explored (Foldi et al, 2020).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Psychedelics have recently been investigated as an alternative treatment for treating various psychiatric conditions with promising results. Most of these studies however suffer from low methodological validity and are mostly open-label, yet they have yielded preliminary evidence for the capacity of psychedelic substances for treating addiction, depression, anxiety, and eating disorders (29)(30)(31)(32)(33)(34)(35). In recent years, several randomised controlled trials (RCTs) have robustly demonstrated ayahuasca, ketamine and psilocybin's potent anti-depressive effects (36)(37)(38).…”
Section: The Psychedelic Renaissancementioning
confidence: 99%
“…The insula, a brain region that plays a critical role in switching between the salience network, executive control network (ECN) and default mode network (DMN) (Figure 2), known as the 'connector hubs' [159]. The ECN is important for the integration of sensory and memory information, regulation of cognition and behaviour as well as cognitive flexibility [153].…”
Section: Brain Imaging Studies and Cognitive Flexibilitymentioning
confidence: 99%